2008
DOI: 10.25011/cim.v31i4.4778
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine ameliorates radiation-induced oxidative lung damage in rats

Abstract: Clin Invest Med 2008; 31 (4): E182-E188.Abstract Purpose: To investigate the possible protective effects of aminoguanidine (AG ) on lung damage in whole body irradiated rats. Methods: To evaluate the biological damage of radiation on rat lung tissue, lipid peroxidation products were measured using biochemical parameters. Thirty Wistar albino rats were divided into three subgroups: control (C) , irradiation alone (RT), and RT + AG combined. After sacrificing the rats, antioxidant enzymes catalase (CAT), superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…11 In a very recent study, 12 aminoguanidine has been shown to reduce cisplatin induced nephrotoxicity due to its antioxidant effect. In another recent study, 13 aminoguanidine has been shown to increase the endogenous antioxidant defence mechanism in rats and protect the animals from radiation-induced lung toxicity. Abdel-Zaher et al 14 have shown that AG markedly inhibits acetaminophen -induced hepatic and renal depletion of antioxidants as well as nitric oxide overproduction.…”
Section: Introductionmentioning
confidence: 95%
“…11 In a very recent study, 12 aminoguanidine has been shown to reduce cisplatin induced nephrotoxicity due to its antioxidant effect. In another recent study, 13 aminoguanidine has been shown to increase the endogenous antioxidant defence mechanism in rats and protect the animals from radiation-induced lung toxicity. Abdel-Zaher et al 14 have shown that AG markedly inhibits acetaminophen -induced hepatic and renal depletion of antioxidants as well as nitric oxide overproduction.…”
Section: Introductionmentioning
confidence: 95%
“…[11][12][13][14][15][16] In a recent study, 17 AG has been shown to reduce cisplatin-induced nephrotoxicity due to its antioxidant effect. In another recent study, 18 AG has been shown to increase the endogenous antioxidant defense mechanism in rats and protect the animals from radiation-induced lung toxicity. AbdelZaher et al 19 have shown that AG markedly inhibits acetaminophen-induced hepatic and renal depletion of antioxidants as well as nitric oxide overproduction.…”
Section: Introductionmentioning
confidence: 97%
“…Oxidative stress is a major factor in the initiation and perpetuation of RILI (20)(21)(22). Our previous expression-profiling data from radiated mouse lungs demonstrated significant deregulation of the redox-sensitive transcription factor NF-E2-related factor-2 (Nrf2) in RILI (23), a key protein in orchestrating cellular antioxidant defenses and maintaining redox homeostasis.…”
mentioning
confidence: 99%